2020
DOI: 10.1159/000512283
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in Her2- Positive Disease

Abstract: <b><i>Background:</i></b> Breast cancer is a heterogeneous disease with well-known characteristics such as hormone receptor (HR) status and human epidermal growth factor (Her)2 status. Although Her2 represents an established treatment target, the development of resistance mechanisms during treatment, cardiotoxicity, and a worse response to standard therapies lead to worse outcomes. <b><i>Summary:</i></b> Therefore, we investigated various biomarkers in breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 67 publications
(96 reference statements)
0
9
0
Order By: Relevance
“…Novel prognostic BC biomarkers have been intensively investigated as recently reviewed by Wu et al (4). In particular, robust biomarkers are in demand for HER2-positive disease to improve selection of patients for current and emerging therapies of HER2-positive metastatic BC (5) as well as for prediction of resistance for anti-HER2 therapies, recurrence (6,7), and particular consequences of the disease (8). Novel approaches based on pathology image analytics and machine learning methods open new perspectives for predictive modeling and clinical decision support (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Novel prognostic BC biomarkers have been intensively investigated as recently reviewed by Wu et al (4). In particular, robust biomarkers are in demand for HER2-positive disease to improve selection of patients for current and emerging therapies of HER2-positive metastatic BC (5) as well as for prediction of resistance for anti-HER2 therapies, recurrence (6,7), and particular consequences of the disease (8). Novel approaches based on pathology image analytics and machine learning methods open new perspectives for predictive modeling and clinical decision support (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that PIK3CA mutations are associated with a poorer prognosis and are more likely to lead to drug resistance. 17 Preclinical studies have implicated that the combination of PI3K/ AKT/mTOR pathway inhibitors can enhance the antiproliferative activity of anti-HER-2 therapy and overcome resistance to anti-HER-2 therapy. [18][19][20][21] The BOLERO-3 study showed that everolimus (mTOR inhibitors) in combination with trastuzumab and vincristine significantly prolonged the PFS of HER2-positive, trastuzumab-resistant patients who previously received paclitaxelbased chemotherapy (7.00 months vs. 5.78 months, p = .0067).…”
Section: Resultsmentioning
confidence: 99%
“…PIK3CA mutations are associated with activation of the PI3K/AKT/mTOR pathway, leading to abnormal activation of this pathway and in turn stimulates tumor proliferation, metastasis, and invasion. Accumulating evidence suggests that PIK3CA mutations are associated with a poorer prognosis and are more likely to lead to drug resistance 17 …”
Section: Discussionmentioning
confidence: 99%
“…HER2 is one of four transmembrane growth factors that comprise the epidermal growth factor receptor (EGFR) family (4). Tumors that overexpress HER2 constitute around one fifth of breast cancers.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Alternatively, aromatase inhibitors decrease the natural conversion of androgens to estrogens in the body – effectively ‘starving’ neoplastic cells of the hormones that would otherwise stimulate their growth. HER2 is one of four transmembrane growth factors that comprise the epidermal growth factor receptor (EGFR) family [ 4 ]. Tumors that overexpress HER2 constitute around one fifth of breast cancers.…”
Section: Introductionmentioning
confidence: 99%